Synthesis of high-performance electrochromic material for facile fabrication of truly black electrochromic devices. (20th January 2021) - Li, Fang-Wei; Yen, Tzu-Chieh; Liou, Guey-Sheng
Abstract: A high-performance electrochromic polyamide, NPTB-PA, derived from N, N ′-bis(4-(dimethylamino)phenyl)- N, N ′-di(4-aminophenyl)-4, 4′-biphenyldiamine (NTPB-diamine) demonstrates important characteristics of multi-oxidation stages and lower oxidation potentials due to the stronger electron-donating ability of dimethylamino groups. Besides, functional hydroxyl groups on the polymer backbone could be conducted via in-situ sol-gel reaction to form covalent bonds between polymer back-bones and precursor of zirconium dioxide (ZrO2 ), and the resulted hybrid films could shorten the switching response time and reduce oxidation redox potentials through electron donor-acceptor system during the electrochemical processes. In addition, anodic electrochromic polyamide NPTB-PA and cathodic heptyl viologen (HV) were introduced into the electrochromic device (ECD) to construct ambipolar system, and the obtained ECD exhibited the panchromatic absorption from transparent to truly black during oxidation (NPTB-PA)/reduction (HV) process with extremely high contrast of transmittance change (ΔT) of 80% over the whole visible-light region. This excellent combination is unique and facile for fabricating novel panchromatic advanced ECD shutter with only two redox-active materials. Graphic abstract: Image, graphical abstract